2015
DOI: 10.1364/oe.23.026095
|View full text |Cite
|
Sign up to set email alerts
|

Low-visibility patterning of transparent conductive silver-nanowire films

Abstract: A partial etching mechanism is proposed to meet the requirement for low-visibility patterning of silver nanowire (AgNW)-based transparent conductive electrodes (TCEs) by reducing the difference in optical properties between conductive and nonconductive regions of the pattern. Using the finite difference time domain (FDTD) method, etched geometries that provide the smallest difference in transmittance after etching are theoretically determined. A sodium hypochlorite-based etchant capable that allows the etched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…The surfactant elimination can be attributed to acetic acid in the chemical mixture solution which washes and etches the surfactant on Ag nanowire surface promoted by the enhanced electron density between PVP and Ag nanowires due to the charge transfer from PVP to Ag nanowires. [ 47–49 ] In order to clarify the effects of PVP removal by acetic acid, chemical treatments with ethanol liquid (used for the solvent of the one‐step chemical treatment), ascorbic acid solution of 1 × 10 −3 m in ethanol, and acetic acid liquid were carried out on Ag nanowires electrode. It was found that only the sheet resistance of Ag nanowires electrode treated by acetic acid has been decreased from 65 to 55 Ω sq −1 as shown in Table S1 (Supporting Information), which means that the surfactants on the Ag nanowires had been removed after the acetic acid treatment as verified by SEM images of Figure S2 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The surfactant elimination can be attributed to acetic acid in the chemical mixture solution which washes and etches the surfactant on Ag nanowire surface promoted by the enhanced electron density between PVP and Ag nanowires due to the charge transfer from PVP to Ag nanowires. [ 47–49 ] In order to clarify the effects of PVP removal by acetic acid, chemical treatments with ethanol liquid (used for the solvent of the one‐step chemical treatment), ascorbic acid solution of 1 × 10 −3 m in ethanol, and acetic acid liquid were carried out on Ag nanowires electrode. It was found that only the sheet resistance of Ag nanowires electrode treated by acetic acid has been decreased from 65 to 55 Ω sq −1 as shown in Table S1 (Supporting Information), which means that the surfactants on the Ag nanowires had been removed after the acetic acid treatment as verified by SEM images of Figure S2 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the wet-etching pattern, the visibility problem can be alleviated by partial etching. The partially etched nonconductive region provides a small difference in transmittance between the conductive and nonconductive regions of the TCF patterns 18 . Additionally, in laser patterning, the laser disconnects the AgNW networks in selective areas, thus electrically insulating the irradiated areas.…”
mentioning
confidence: 99%
“…Recently, transparent electrodes (TEs) such as graphene 8 , graphene-polymer composites 9 , carbon nanotubes (CNTs) 10 , metallic nanowires (MNWs) 11 and metallic mesh film (MMF) 4 , 7 have studied as alternates to ITO. However, graphene and CNTs cannot achieve high transparency and strong EMI shielding simultaneously given that they are carbon-based materials 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%